PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR BIOLOGI SISWA SMS ISLAM TERPADU AL-FITYAN GOWA - Yahya, Husniyati (Jurnal Biotek, 2017)
The Influence of the Implementation of Quantum Teaching Learning Model Towards Biology Learning Result on Eksrection System of Grade XI Students at SMA Islam Terpadu Al-Fityan in Gowa. Quantum teaching learning model is a designed leaning model to further enable students in the learning process. This quantum teaching gives birth to a design framework that TANDUR is an (Abbeviation f grow, natural, named, demonstrate, repeat and celebrate). The study aints at examining the influence of the implementation of quantum teaching model towards student learning result in learning Biology. The stdudy is a quasi experiment. e population of the study was grade XI IPA students of the second semester of academy year 2016/2017 at SMA IT Al-Fityan Gowa. Samples where taken b employing random class. The result of the study reveal that the implementation of quantum teaching model gives significant influence towards student learning Biology result.